1984
DOI: 10.1002/clc.4960070108
|View full text |Cite
|
Sign up to set email alerts
|

The effect of radiographic contrast agents on bleeding time and platelet aggregation

Abstract: Summary:The purpose of this study was to determine whether the use of relatively small amounts of radiographic contrast agents may impair hemostasis. Before and after injection of contrast agents, we measured the template bleeding time, platelet count in whole blood and platelet-rich plasma, platelet aggregation induced by epinephrine and adenosine diphosphate (ADP). and percent disaggregation of ADP-induced platelet aggregates in platelet-rich plasma of 18 patients. Ten patients received 50-100 ml of sodium i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
(4 reference statements)
1
4
0
Order By: Relevance
“…However, a 1982 French study employing significantly lower RCM concentrations, showed ioxaglate to be the most consistent inhibitor of platelet aggregation, while diatrizoate appeared to promote platelet aggregation, though the increase was not staistically significant [5]. Shortly thereafter, two separate groups of investigators reported no effect of diatrizoate on platelet aggregation in vitro and ex vivo [7,12]. The amount of contrast agent used in these studies was comparable to that in previous reports.…”
Section: Aggregation Kineticssupporting
confidence: 66%
See 1 more Smart Citation
“…However, a 1982 French study employing significantly lower RCM concentrations, showed ioxaglate to be the most consistent inhibitor of platelet aggregation, while diatrizoate appeared to promote platelet aggregation, though the increase was not staistically significant [5]. Shortly thereafter, two separate groups of investigators reported no effect of diatrizoate on platelet aggregation in vitro and ex vivo [7,12]. The amount of contrast agent used in these studies was comparable to that in previous reports.…”
Section: Aggregation Kineticssupporting
confidence: 66%
“…[ l ] However, there are several reports of inhibition by contrast agents of platelet aggregation, [3-111 while Verdirame et al [12] and Shapiro et al [13] found no effects.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][32][33][34] We have demonstrated previously that the use of a low-osmolarity nonionic contrast agent was associated with increased thrombus formation during coronary angioplasty in humans. 24 This observation suggested the hypothesis that contrast agents might influence the effect of balloon dilation on platelet activation and that different agents might have different effects.…”
Section: Effects On Contrast Mediamentioning
confidence: 94%
“…Different contrast media have been found to have different effects on in vitro platelet function. [2] Previous studies have suggested that the use of different contrast media is associated with different rates of thrombus formation during angioplasty, suggesting that different effects of contrast agents on platelet function and thrombosis demonstrated in vitro may have important clinical implications. [3] During angiography, blood is transiently replaced by the contrast media, which also rapidly reaches the vascular smooth muscles and affects different elements of the blood and blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…[1] In vitro studies have demonstrated that contrast media have noticeable effects on platelet function and thrombosis and that these effects differ between various contrast agents. [2] …”
mentioning
confidence: 99%